2011
DOI: 10.1177/0194599811426089
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Acute Rhinosinusitis

Abstract: RARS may affect approximately 1 in 3000 adults per year. Despite significant direct health care costs of more than $1000/year per individual patient with RARS, nasal endoscopy and computed tomography are not commonly obtained early after potential diagnosis. RARS is likely an underdiagnosed condition warranting further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Our results are similar to those from a retrospective cohort study from Brazil, which found that ART comprising three antiretrovirals was associated with a significantly lower prevalence of otorrhea (7.1%) than children receiving only one or two antiretrovirals (20.8%) (p = 0.02) [7]. The mean age in this study was 6.6 (± 2.5) years, far older than in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results are similar to those from a retrospective cohort study from Brazil, which found that ART comprising three antiretrovirals was associated with a significantly lower prevalence of otorrhea (7.1%) than children receiving only one or two antiretrovirals (20.8%) (p = 0.02) [7]. The mean age in this study was 6.6 (± 2.5) years, far older than in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Both occur frequently in HIV-infected children [4-6]. Antiretroviral therapy (ART) was associated with a reduction in otitis media and CSOM in a retrospective cohort [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Acute rhinosinusitis is an important health problem that seriously affects the quality of life of sufferers, and represents a considerable economic burden for society [ 1 , 2 ]. Although many studies on the mechanisms of acute rhinosinusitis have been carried out, they are not yet clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…1 The aggregated cost of rhinosinusitis is approximately 8.6 billion dollars annually, and the disease affects an estimated 16% of the population in the United States. 1, 2 In addition to the financial burden on the health system, quality of life and health utility studies have shown significant morbidity associated with rhinosinusitis, comparable to that of other chronic illnesses such as congestive heart failure and chronic obstructive pulmonary disease (COPD). 3, 4 The loss of the sense of smell, which often accompanies chronic rhinosinusitis (CRS), further compromises quality of life.…”
mentioning
confidence: 99%